Tinjauan Line Stop Mold pada Proses Produksi Part Moulding Quarter Window Upper di PT. Autoplastik Indonesia - Angga Setya Prawira; Dene Herwanto (Peneliti.net, 2021)
PT. Autoplastic Indonesia is a manufacturing company that produces various automotive components made from plastic. PT. Autoplastic Indonesia uses 3 lines, namely the plastic injection line, painting line, and assembling line. However, there is damage to the mold that causes a line stop or the production process stop, so that it can cost time and material. With this research, it is expected d to find out the causes and consequences of problems that occur in the mold system that is used as a mold to make these products so that repairs can be made to damage quickly and permanently and there will be no long and detrimental line stops. The results of this study indicate that the damage experienced by this mold affects the production process and causes defects in the product in the form of silver defects caused by operators who are negligent in checking the conditions that occur. This silver defect arises due to delays in filling the material in the hopper and is also caused by damp material